PENGARUH LAMA FERMENTASI DAN KONSENTRASI SUKROSA TERHADAP SIFAT FISIKOKIMIA DAN SENSORI TEH KOMBUCHA KULIT PELEPAH ALOE VERA - haryanto, mochammad mulia (Fakultas Pertanian Universitas Tanjungpura, 2014)
ABSTRACT The aim of this research was to found out the lengthy fermentation and sucrose concentration to produce phsysicochemical properties and sensory the best ones for fickle aloe vera leaves in kombucha tea aloe vera leaves. This research used a Completely Randomized Design with factorial pattern (two factors). The first factor was the lengthy fermentation (2, 4 and 6 days), and sugar concentration (9%. 12% and 15%) with 3 replication. Variables observed were the total soluble solid, pH, total acid, vitamin C and sensory analysis. Observational data obtained in the study results were statistically analyzed by F test (ANOVA) with a 5% level test. If significant treatment, followed by a test of Honestly Significant Difference (HSD) at 5% level. Sensory outcome data were analyzed using Kruskall-Wallis method, then to get the best treatment to test the effectiveness of the index. The best treatment was the combination of 6 days of fermentation and concentration of sucrose 15% this kombucha leaves aloe vera tea had 9,73obrix total soluble solid, pH 3,74, 3,25% total acid, vitamin C 5,28 (mg/100g) and the result sensory analysis which is brownish yellow coloured, with aromatic value is smell sting acid, sweetnes value is sweet less, acidity value is acidish sour, fond ness value is kinda like. Keywords:kombucha leaves aloe vera tea, lengthy fermentation, phsysicochemical, sensory, sucrose concentration